Projects without boundaries : successfully leading teams and managing projects in a virtual world - Martinelli, Russ J., 1959-; Waddell, James M., 1946-; Rahschulte, Tim (John Wiley & Sons, Inc., 2017)
Clear, proven solutions for virtual project management challenges Projects Without Boundaries offers project managers a clear framework for bringing both project management practices and project team leadership principles to the virtual space. Written by a team of authors with years of experience managing nationally and internationally distributed teams, this book provides a suite of best practices, checklists, and actionable strategies for managing a project and building a high-performing team in a virtual and multicultural environment. Real-world examples illustrate the application of the concepts discussed, and the Virtual Project Readiness Assessment facilitates both team evaluation and transformation planning for virtual project management improvement. Each chapter focuses on the critical challenges encountered while managing virtual projects and details proven solutions that improve a virtual organization, boost project performance, and facilitate positive outcomes. Globalization and technological advances have merged to create dynamic, productive teams that work together from around the globe; this opportunity can bring great difficulty for project managers, who must negotiate hurdles that no not exist on traditional projects. This book provides ready-made solutions specific to distributed and multicultural teams, to help you achieve the full potential of the global talent pool.-Overcome common challenges of virtual projects with distributed teams -Navigate complex team dynamics to ensure effective collaboration -Work seamlessly across borders, time zones, and cultures -Determine optimal virtual communication and collaboration tools -Apply traditional project management practices in a virtual setting A team fails or thrives on the strength of its management. Fitting the group's needs, expectations, personalities, and skills into a cohesive whole is seldom simple - and distance adds an additional layer of complexity. Projects Without Boundaries provides expert guidance on keeping it together, with proven practices, tools, and virtual team leadership strategies.